Ability to Learn Indonesian Language Through Online Zoom Application System in SMP Negeri 14 Medan - Pulungan, Rosmilan; Syarif, Hermawati (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
Indonesia is currently faced with the challenge of the Covid-19 pandemic, in which the government urges the Indonesian people to stay at home. So that learning activities that were originally carried out face-to-face turned into non-face-to-face learning. This study uses descriptive research methods with qualitative analysis techniques. The purpose of this research is to reveal events or facts, circumstances, phenomena, variables and circumstances that occurred during the research by presenting what actually happened. This study uses descriptive research methods with qualitative analysis techniques. The instrument in this study was a questionnaire that was proposed to the sample. With a total of 20 questions, each question is given a score of 5 so that the highest score in this test is 100. The results of this study are the implementation of online learning in class VIII AD SMP Negeri 14 Medan is less effective, especially in learning Indonesian, because in the implementation of online learning students only given the task of working on evaluation questions and only occasionally practice, and the teacher does not know whether the students really understand or not. Considering that students study at home accompanied by their parents or guardians, it is possible that students’ assignments are assisted by their parents or guardians.